Chapa, J.O. (2022). Is Remote Warfare Moral? Weighing Issues of Life + Death from 7,000 Miles - Cronshaw, Darren (Health and Social Care Chaplaincy, 2025)
Chapa, J.O. (2022). Is Remote Warfare Moral? Weighing Issues of Life + Death from 7,000 Miles. New York: PublicAffairs, Hachette Book Group, 288 pp. (hbk). ISBN: 9781541774452.